Influence of female and male age and association periods of the adults of oriental armyworm (Lepidoptera: Noctuidae) on oviposition, egg hatch and longevity. - Singh, Ram; Chaudhary, J. P. (Contributions to Entomology = Beiträge zur Entomologie, 1991)
The differential age (1, 5, 10, 15, 20, 25 days old) of the oriental armyworm Mythimna separata (Wlk.) females and males at mating significantly influenced oviposition period, egg output and hatching when studied under laboratory conditions (17 ± 2 °C, 71 ± 5% R.H., 10% sucrose diet). Younger the adults (10 d) at mating higher was the egg deposition and hatching but it was accomplished when association period of both females and males was more than 5 days at a stretch. Association period of 20 days or mor yielded higher number of eggs (818-915 egg/female) as compared to 1-5 days (10-250 egg/female).